A cobertura florestal e o tipo ambiental moldam a diversidade funcional de aves insetívoras dentro da Mata Atlântica do sudeste brasileiro - Manzoli, Enzo Coletti (Universidade Federal de São Carlos, 2023)
Arthropod-eating birds are a heterogeneous group, with different levels of environmental sensitivity and diverse responses to habitat degradation. In this paper, we tested the effects of landscape on the functional diversity of insectivorous birds within the Brazilian Atlantic Forest. We predict that (I) species composition and functional diversity are shaped by turnover and nestedness across different habitats, and (II) the gradient of forest cover has a positive effect on bird species composition and functional diversity. We used data from 22 landscapes of the Atlantic Forest in the Cantareira-Mantiqueira region (Brazil), within buffers of 1 km radius, surrogating three types of environments (i.e., forests, pastures, and marshes). The components of β-functional diversity were calculated using the beta pair and beta multi-function for each type of environment, and the effects of the forest cover gradient and environment type were tested using linear models and GLMM, respectively. Our results showed that the forest cover gradient and the type of environment had a negative effect on the indices of functional diversity, contrary to our expectations. Pasturelands and marshes were susceptible to turnover and nestedness, respectively. The beta diversity of forests was influenced by both species nestedness and turnover. The regional native forest fragments are generally small-sized, and in early successional stages, which could explain the patterns we found. The presence of secondary forests may have affected the expected pattern of functional diversity, therefore, caution is needed when interpreting this, since the way in which compensatory dynamics may not involve real functional compensation.
Forest cover and environmental type shape functional diversity of insectivorous birds in Atlantic Forest of southeastern Brazil
Keywords: Aves insetívoras; Cobertura florestal; Diversidade funcional beta; Diversidade funcional; Mudança na paisagem; Beta functional diversity; Forest cover; Functional diversity; Insectivorous birds; Landscape change; CIENCIAS BIOLOGICAS::ECOLOGIA::ECOLOGIA TEORICA